A case report of primary complex anal fistula with 7 external openings treated with combined preoperative 3D MRI model. Issue 11 (17th March 2023) - Hong, Yongping; Qiu, Yonggang; Li, Guofeng
Abstract : Introduction: Anal fistula is a common perianal disease, but primary complex anal fistulas with 7 external openings is extremely rare. Patient concerns: We report a case of a 36-year-old man with a 10-year history of recurrent pus flow from paranal mass. Diagnosis: Primary complex anal fistula. Interventions: The patient underwent fistulotomy plus seton, which we successfully completed with the aid of 3-dimensional (3D) reconstruction model created from magnetic resonance imaging (MRI). Outcomes: The wound healed well and there was no recurrence 8 months after surgery. Conclusion: In the treatment of complex anal fistula, the combined application of 3D MRI model will be beneficial to obtain better surgical results.